Chromatography Perspective and Optical Illusion Renaissance to Contemporary Painting (Damascus University Journal for engineering sciences, 2021)
This research focuses on the new perception of the concept of the place that was crystallized in visual arts, especially painting. Since the Renaissance through to Impressionism and Contemporary Painting, the artwork in the figurative painting depended on the transformation from flat perceptive imaging to deeper and more three dimensional portrayal which focuses on emphasizing size. The Renaissance period marked the beginning for the research on 3D presentation on a flat surface, which was applied for the first time on painting during the first half of the fifteenth century. Over time, we notice the evolution of the perspective concept in drawing and portrayal. This concept morphed into several shapes, from linear perspective and color perspective to pointillism which depended on the visual arts that developed later to optical illusions which is now considered one of the modern techniques in art. This technique depends on visual deception that influence our visual and sensory perceptions through either composite geometric shapes with sharp border such as cubes, rectangles, triangle, circles, and cones; or the use of two-shades contrasting colors; or through a combination of multiple colors or 2D/3D straight, undulating and overlapping lines. By the early fifties, the optical illusion has become characteristic of one contemporary art movement founded by Victor Vasarelly. However, this form of art did not appear from nowhere; rather, it was a natural progression of the abstract movement, which adopted different aesthetic values such as balance, rhythm, contrast, and depth. This visual art is still in constant development, taking on several different dimensions with the passage of time
Keywords: Perspective; Chromatography; perspective; Victor Vasarelly